The Philosophy of Logical Atomism A Centenary Reappraisal (History of Analytic Philosophy, 2018)
This book offers a comprehensive critical survey of issues of historical interpretation and evaluation in Bertram Russell's 1918 logical atomism lectures and logical atomism itself. These lectures record the culmination of Russell's thought in response to discussions with Wittgenstein on the nature of judgment and philosophy of logic and with Moore and other philosophical realists about epistemology and ontological atomism, and to Whitehead and Russell's novel extension of revolutionary nineteenth-century work in mathematics and logic. Russell's logical atomism lectures have had a lasting impact on analytic philosophy and on Russell's contemporaries including Carnap, Ramsey, Stebbing, and Wittgenstein. Comprised of 19 original essays, this book will demonstrate how the direct and indirect influence of these lectures thus runs deep and wide.